Roles of AMPA receptors in social behaviors - Xu, Qi Wei; Larosa, Amanda; Wong, Tak Pan (Frontiers in Synaptic Neuroscience, 2024)
As a crucial player in excitatory synaptic transmission, AMPA receptors (AMPARs) contribute to the formation, regulation, and expression of social behaviors. AMPAR modifications have been associated with naturalistic social behaviors, such as aggression, sociability, and social memory, but are also noted in brain diseases featuring impaired social behavior. Understanding the role of AMPARs in social behaviors is timely to reveal therapeutic targets for treating social impairment in disorders, such as autism spectrum disorder and schizophrenia. In this review, we will discuss the contribution of the molecular composition, function, and plasticity of AMPARs to social behaviors. The impact of targeting AMPARs in treating brain disorders will also be discussed.